Designing Dynamic Interventions to Improve Adherence in Pediatric Long-Term Treatment – The Role of Perceived Value of the Physician by Primary Caregivers. Issue 14 (6th December 2021) - Venkatraman, Krithika; Vijayalakshmi, V.; Sudarsanam, Nandan; Manoharan, Anand
ABSTRACT: Primary Caregivers are the fulcrum in the physician-caregiver-child triad. Existing literature discusses static multi-component interventions in detail. In long-term treatments, dynamic intervention design is needed as the environment and situations of the families are dynamic. The objectives of this study are (a) to identify the components of the primary caregiver's perception of the physician's value with reference to the effectiveness of consultation and relationships with the former and with the child; (b) to establish the role of this perception in designing dynamic interventions, and (c) to describe the perception's potential influence on adherence. A PRISMA, chronological, and morphological analysis of the literature is carried out about caregivers' adherence in the pediatric long-term treatment context. We define communication and consultation as the functional, whereas relationship as the emotional component of the caregiver's perception of the physician. We propose a theoretical model that incorporates intervention as an integral component of care. Adherence happens as a response to changing situations and hence fluctuates. Hence, a dynamic intervention design to benefit the child should be incorporated into care through the caregiver-physician bridge. Future research should explore how intervention needs change and the driving reasons for understanding the static and dynamic components of interventions.